Pengaruh Kualitas Pengungkapan Corporate Social Responsibiliy terhadap Nilai Perusahaan dengan Kepemilikan Asing sebagai Variabel Moderasi: Studi Empiris pada Perusahaan Pertambangan yang Terdaftar di BEI Periode 2021 - 2024 - Rahma, Rahma; Pebriyani, Dewi (Universitas Negeri Padang, 2025)
This study examines the effect of corporate social responsibility (CSR) disclosure quality on firm value, with foreign ownership as a moderating variable. The study focuses on mining companies listed on the Indonesia Stock Exchange during the 2021–2024 period. Using purposive sampling, 25 companies were selected, resulting in 100 firm-year observations, and analyzed using moderated regression analysis (MRA). The findings indicate that CSR disclosure quality has a negative and significant effect on firm value, suggesting that higher CSR reporting quality may not be appreciated by the market and may even be perceived as a cost. However, foreign ownership positively moderates this relationship, suggesting that the presence of foreign investors strengthens governance and transforms CSR reporting into a long-term value creation mechanism. These results contribute to the literature by integrating CSR disclosure quality as measured by the GRI Standards with foreign ownership, a rarely examined approach in the Indonesian mining sector. Future studies are recommended to expand the cross-sector scope and complement the quantitative analysis with qualitative approaches.